2017
DOI: 10.3906/vet-1512-96
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of foot-and-mouth disease virus excretion in the milk ofapparently healthy vaccinated buffaloes in Islamabad, Pakistan

Abstract: The aim of the study was to determine the seroprevalence of foot-and-mouth disease (FMD) and isolation of the FMD virus (FMDV) in the milk of apparently healthy Asian buffaloes. A cross-sectional study was conducted in periurban dairy farms (n = 20) on ≥20 animals per farm in the suburbs of Islamabad, Pakistan. Sera samples (n = 200) were collected to monitor FMDV seroconversions. The analysis of serum samples using ELISA indicated a high seroprevalence of FMD (78%; 156/200) in Asian buffaloes. Milk samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This might help explain the phenomena seen in FMDV-enzootic contexts, where seroprevalence rises without disease (Bertram et al, 2018), and where outbreak reporting imperfectly predicts seroprevalence (van Andel 2020b). The observation that healthy dairy cattle and buffalo shed virus in their milk (Nawaz, 2019;Ahmed 2017), raises the possibility that in endemic countries, some cattle might be exposed from birth to both virus and protective maternal antibody. Additionally, intensive sampling of buffalo in a dairy colony in Pakistan demonstrated that within one year numerous serotypes and strains could move through a herd without any clinical signs of infection (DOI: 10.1111/tbed.12963).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might help explain the phenomena seen in FMDV-enzootic contexts, where seroprevalence rises without disease (Bertram et al, 2018), and where outbreak reporting imperfectly predicts seroprevalence (van Andel 2020b). The observation that healthy dairy cattle and buffalo shed virus in their milk (Nawaz, 2019;Ahmed 2017), raises the possibility that in endemic countries, some cattle might be exposed from birth to both virus and protective maternal antibody. Additionally, intensive sampling of buffalo in a dairy colony in Pakistan demonstrated that within one year numerous serotypes and strains could move through a herd without any clinical signs of infection (DOI: 10.1111/tbed.12963).…”
Section: Discussionmentioning
confidence: 99%
“…For example, while 90% of FMDV-infected naive cattle would be expected to develop disease upon exposure, FMDV-exposed cattle in an unvaccinated herd in Cameroon had a seroprevalence increase of 30% over a twelve month observation period, despite the fact that only 6 of 100 animals were noted to have FMD-associated lesions during this time (Bertram et al, 2018). In addition, clinically-healthy cattle and buffalo from Pakistan produced milk containing live FMDV up to 6 months following FMD outbreaks on the same farms (Nawaz, 2019;Ahmed 2017). These examples suggest that cattle and buffalo exposed early and frequently to FMDV might exist in a different relationship with the virus than is commonly understood in an epidemic context.…”
Section: Introductionmentioning
confidence: 99%
“…During the study period, vaccination was carried out in response to an outbreak. Whether vaccination in these herds TA B L E 3 Univariate mixed effect logistic regression analysis for association with a positive FMD rRT-PCR result for the total study area may increase the likelihood of sub-clinical infection is unknown, although there have been reports of sub-clinical infection in vaccinated animals (Donaldson & Kitching, 1989;Hutber, Kitching, & Conway, 1999;Lyons et al, 2017) and virus excretion in the milk of apparently healthy vaccinated animals (Ahmed et al, 2017).…”
Section: Yes No Totalmentioning
confidence: 99%
“…Previous studies have demonstrated that the mammary gland is highly susceptible to FMDV replication (Burrows, Mann, Greig, Chapman, & Goodridg, ) and that FMDV can be detected by real‐time reverse transcription polymerase chain reaction (rRT‐PCR) assays in milk from experimentally infected cattle, before and during the appearance of clinical signs, and up to 28 days post‐infection (Armson et al, ; Reid et al, ). FMDV RNA has also been detected in milk samples from naturally infected cattle (Armson et al, ; Ranjan et al, ; Saeed et al, ) and buffaloes (Ahmed et al, ) in endemic settings. Furthermore, using individual milk samples collected from naturally infected cattle in northern Tanzania, it has been demonstrated that VP1 sequences could be obtained, corresponding with those generated from clinical samples collected from lesions from the same animal (Armson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a small number of studies have described the detection of FMDV RNA in milk from naturally‐infected animals. These include FMDV detection in milk during the 2007 FMD outbreak in the United Kingdom (Armson et al., ), in cattle and buffaloes in Pakistan (Ahmed et al., ; Saeed et al., ) and in cattle in India (Ranjan et al., ). The limited milk samples used in these studies were collected either as an additional sample type to validate molecular assays, or to investigate the possible role of milk in FMDV transmission; nonetheless these studies provide useful evidence that FMDV RNA can be detected and typed by rRT‐PCR, in milk from naturally infected animals.…”
Section: Fmdv Detection In Milk Samples and Epithelial Samplesmentioning
confidence: 99%